L’aigle et le castor : étude de la distribution spatiale de la criminalité aux États-Unis et au Canada - Ouimet, Marc (Criminologie, 1993)
In the last three decades, a number of researchers have undertook the comparison of American and Canadian crime rates. Among them, Lipset (1990) and Hagan (1991) have shown that violence was more frequent south of the border than north of it. To explain why crime was more frequent in the US than in Canada, those authors argued that differences in values and culture of each country's residents was the principal determinant of this situation. Using regional and infranational disaggregated crime rates, this article shows that differences in both country's crime rates are not univocal. For example, crime rates in Canada are not higher than those of Northern United States for three crimes out of four studied. What makes US crime rates appear much higher than the Canadian ones can be attributable to a small number of States and cities which have extraordinarily high crime rates.